Targeting the Exonic Circular OGT RNA/O-GlcNAc Transferase/Forkhead Box C1 Axis Inhibits Asparagine- and Alanine-Mediated Ferroptosis Repression in Neuroblastoma Progression - Qilan Li; Yang Cheng; Chunhui Yang; Minxiu Tian; Xiaojing Wang; Dan Li; Xinyue Li; Jiaying Qu; Shunchen Zhou; Liduan Zheng; Qiangsong Tong (Research)
The disruption of ferroptosis, an emerging form of programmed cell death, is crucial in the development and aggressiveness of tumors. Meanwhile, the mechanisms and treatments that control ferroptosis in neuroblastoma (NB), a prevalent extracranial cancer in children, are still unknown. In this study, forkhead box C1 (FOXC1) and O-GlcNAc transferase (OGT) are identified as regulators of asparagine- and alanine-mediated ferroptosis repression in NB. Mechanistically, OGT facilitates FOXC1 stabilization via inducing O-GlcNAcylation in liquid condensates to increase the expression of asparagine synthetase (ASNS) and glutamate pyruvate transaminase 2 (GPT2), resulting in asparagine and alanine biogenesis, and subsequent synthesis of cystathionine β-synthase (CBS) or ferritin heavy chain 1 (FTH1). Meanwhile, exonic circular OGT RNA (ecircOGT) is able to encode a novel protein (OGT-570aa) containing domain essential for binding of OGT to FOXC1, which competitively decreases the OGT–FOXC1 interaction. Preclinically, miconazole nitrate facilitates the interaction of OGT-570aa with FOXC1, suppresses ferroptosis resistance of NB cells, and inhibits their growth, invasion, and metastasis. In clinical NB cases, higher OGT, FOXC1, ASNS, GPT2, CBS, or FTH1 levels are correlated with worse survival, while lower ecircOGT or OGT-570aa expression is associated with tumor progression. These results indicate that targeting the ecircOGT/OGT/FOXC1 axis inhibits asparagine- and alanine-mediated ferroptosis repression in NB progression.